Answer:
One can be 95% confident that the drive-through service times of fast-food chain is between 169 seconds and 172 seconds.
Step-by-step explanation:
The confidence interval gives a range of value for the population mean or parameter, which is calculated from the statistic value of the data (that is sample statistic). This range gives the interval which is associated with a certain level of confidence for which the interval will contain the true value of the unknown parameter (true value). In the scenario above, the associated confidence level is 95%.Hence, we can be 95% confident that the true value will be continued with the interval (169 ; 172)
Answer:
Rule: replace x by x - a where a is the number of units that you want to move right. a must be greater than 0. x - - a would move left.
Step-by-step explanation:
You want f(x) to move 3 units to the right.
That would mean that x would be replaced by x - 3. Just to be sure let's try it.
- Suppose you have f(x) = x^2 + 6x + 5 It is graphed as the red line
- Now suppose you want to move 3 units right.
- It would replaced like f(x - 3) = (x - 3)^2 + 6(x - 3) + 5 which is the blue line
- Notice nothing else is changed. The blue line looks exactly like the red line except that it is shifted 3 units to the right.
10. 14
2 * 7 <==
11. 12
6 * 2
2 * 3 * 2 = 2^2 * 3 <==
12. 15
3 * 5 <==
13. ur gonna have 3 tables that each have 4 chairs
Hello there!
Yes, your solution is correct! A way to check it is replacing the value you found for x into x in the equation.
3(2-x) = 7 - 4x ⇒ 3(2-1) = 7 - 4(1)
And now solve 3(2-1) = 7 - 4(1).
3(1) = 7 - 4(1)
3 = 7 - 4
3 = 3
Since it is a true statement that 3 is equal to 3, it means your solution of x = 1 is correct. Good job! :)
Answer:
f(n) = f(n - 1) + 3
Step-by-step explanation:
Substitute
to get the recursive formula.
OPTION 1: f(n) = f(n - 1) + 3
Substituting n = 1.
f(1) = f(1 - 1) + 3 = 0 + 3 = 3.
Substituting n = 2.
f(2) = f(2 - 1) + 3 = f(1) + 3 = 3 + 3 = 6.
Substituting n = 3.
f(3) = f(3 - 1) + 3 = f(2) + 3 = 6 + 3 = 9.
The numbers match the given sequence. So, we say the above recursive formula represents the sequence.
OPTION 2: f(n) = f(n - 1) + 2
Substituting n = 1
f(1) = f(0) + 2
3.
So, this is eliminated.
Similarly, OPTION 3 and OPTION 4 can be eliminated as well.